2019
DOI: 10.1038/s41416-019-0403-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer mortality in synchronous bilateral breast cancer patients

Abstract: BACKGROUND: Evidence suggests that patients with synchronous bilateral breast cancer (SBBC), diagnosed within 4 months, have an inferior prognosis compared to unilateral breast cancer (UBC) patients. Using data from nationwide Danish clinical databases, this cohort study investigated whether the inferior prognosis could be explained by SBBC patients having a more aggressive disease, or whether the prognosis could be explained by the fact that they have two simultaneous cancers. METHODS: Patients were diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
2
26
0
1
Order By: Relevance
“…The impacts of bilateral breast cancer on adverse prognosis such as disease recurrence, distant metastasis, and overall survival have been reported with conflicting results [ 9 , 10 ]. Because appropriate treatment and surveillance are required to reduce the risk and potential adverse prognosis, understanding of the clinical course of bilateral breast cancer is very important [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of bilateral breast cancer on adverse prognosis such as disease recurrence, distant metastasis, and overall survival have been reported with conflicting results [ 9 , 10 ]. Because appropriate treatment and surveillance are required to reduce the risk and potential adverse prognosis, understanding of the clinical course of bilateral breast cancer is very important [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of bilateral breast cancer among all breast cancers is modest and ranges, for example, from 2.2% in a Dutch screening population to 4.4% in a population derived from the National University of Ireland Galway breast cancer database in Ireland 1‐4 . A worse survival has been reported for women with bilateral breast cancer than for women diagnosed with unilateral breast cancer 5‐11 …”
Section: Introductionmentioning
confidence: 99%
“…SBBC accounts for 2-11% of all breast cancer cases, and the estimated risk of SBBC development is 2-6 times higher in patients already diagnosed with breast cancer 2,3 . Several clinical studies have found that compared to patients with unilateral breast cancer (UBC), SSBC patients have higher rates of distant metastasis and lower overall survival [2][3][4][5][6][7] . In 2015, Jobsen and colleagues reported that the aggressiveness of primary tumors in SBBC patients does not appear to differ from UBC patients, as measured by malignancy grading, mitotic activity index, hormone receptor status, and the presence of positive lymph nodes 2 .…”
Section: Introductionmentioning
confidence: 99%